Measurement of prompt D-meson production in p−Pb collisions at √sNN=5.02 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (Physical review letters, 2014)
The pT-differential production cross sections of the prompt charmed mesons D0, D+, D*+, and D+s and their charge conjugate in the rapidity interval −0.96<ycms<0.04 were measured in p−Pb collisions at a center-of-mass energy √sNN=5.02 TeV with the ALICE detector at the LHC. The nuclear modification factor RpPb, quantifying the D-meson yield in p−Pb collisions relative to the yield in pp collisions scaled by the number of binary nucleon-nucleon collisions, is compatible within the 15%-20% uncertainties with unity in the transverse momentum interval 1<pT<24 GeV/c. No significant difference among the RpPb of the four D-meson species is observed. The results are described within uncertainties by theoretical calculations that include initial-state effects. The measurement adds experimental evidence that the modification of the momentum spectrum of D mesons observed in Pb-Pb collisions with respect to pp collisions is due to strong final-state effects induced by hot partonic matter.
*ALICE Collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glässel, J. Klein, L. Leardini, D. Lohner, X.-G. Lu, A. Maire, J. Mercado Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, S. Vallero, M. Völkl, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 925 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel ist der Buchstabe s hochgestellt
Gesehen am 06.10.2020